SOSIALISASI DAN PERENCANAAN TEKNIK RUANG TERBUKA HIJAU (RTH) SKALA RW DI KOMPLEK GRAHA RANCAMANYAR, RW 18 DESA RANCAMANYAR KECAMATAN BALEENDAH KABUPATEN BANDUNG - Azis Ali Wibowo; Asep Setiawan; Bambang Eko Widyanto; Fuad Hasan; Raden Herdian Bayu Ash Siddiq; Yanyan Agustian (Jurnal Abdi Insani, 2026)
Graha Rancamanyar Housing Complex RW 18, located in Rancamanyar Subdistrict, Baleendah District, Bandung Regency, is an area prone to flooding due to inadequate stormwater runoff management. The settlement lacks optimal management of Green Open Space (GOS) because of limited community understanding of its ecological and sociocultural functions, as well as the absence of data on the extent and distribution of existing GOS areas. These issues underscore the urgency of providing and managing GOS as a strategy for flood mitigation and for supporting community sociocultural activities. This activity aims to enhance community awareness of the importance of GOS through the development of a technical design at the RW scale using participatory and visual approaches to strengthen understanding of the ecological and sociocultural functions of GOS. The activity was implemented through six stages: preparation, field surveys to measure the area of GOS and non-green open spaces (NGOS), technical planning of GOS, socialization on GOS, and the provision of funding and equipment for GOS maintenance. These stages applied an implementative and participatory approach to ensure community involvement and the sustainability of GOS management at the RW level. The socialization activity, attended by 25 participants, improved residents’ and developers’ understanding of the importance of GOS and their responsibilities in its management. Field measurements generated previously undocumented data on existing GOS, totaling 64,559.16 m² or 25.31% of the total area of RW 18. Residents actively participated in the development of the technical GOS design, which included zoning arrangements for arts, sports and health, sociocultural functions, playgrounds, pet spaces, and healing areas. Financial support and maintenance equipment, such as grass cutters, were well received and utilized by residents. The program also encouraged the establishment of an RW-based environmental maintenance group. The series of community service activities successfully identified deficiencies in the GOS area in RW 18, where the required minimum threshold for GOS is 30% in accordance with Ministry of Public Works Regulation No. 5 of 2008 and Regulation No. 12 of 2009. The program also produced a technical GOS design and strengthened community capacity in participatory and sustainable GOS management.